Functional Importance of Seed Weight on the Seedling Establishment of Syzygium bankense (Hassk.) Merr. & L.M. Perry and Quercus gemelliflora Blume - ANNISA SATYANTI (Biodiversitas Journal of Biological Diversity, 2009)
Seedling is the first and prominent phase of plant development. Seedling performance can be determined by seed and itsembedded characteristics, among them is seed weight. In this study we would like to see how seed weight within species affect seedling establishment. The hypotheses tested were that heavier seed is regarded advantageous compared to lighterseed by functionally produce more competitive seedlings for better growth. Heavier seeds indeed resulted in higher shootlength than lighter seeds. The same pattern was also pronounced for the correlation between seed weight and shoot length of Syzygium bankense and Quercus gemelliflora. There was also a significant positive correlation between seed size andnumber of leaf within species.Key words: seed weight, Syzygium bankense, Quercus gemelliflora, seedling establishment, germination